Development of PBL-Based Student Worksheets to Improve Problem-Solving Skills and Collaborative Skills of 11th Grade Students in Reaction Rate Material - Erna Yupeni; Susilawati Susilawati; Dedi Futra (AL-ISHLAH: Jurnal Pendidikan, 2025)
Problem-solving and collaboration are essential 21st-century skills, particularly in chemistry education where students must grasp abstract and complex topics like reaction rates. This study aims to develop Problem-Based Learning (PBL)-based Lembar Kerja Peserta Didik (LKPD, student worksheets) to enhance these skills among Grade XI students. The research employed a Research and Development (RD) approach using the ADDIE model. Data were collected through interviews, questionnaires, validation sheets, and user response surveys. Three subject matter experts conducted the validation. Small-scale trials were performed with three students of varying abilities. Large-scale testing used a quasi-experimental pretest-posttest control group design involving 36 Grade XI science students from SMAN 5 Pinggir, selected purposively. User feedback was obtained from three teachers and 30 students across three schools. The developed LKPD achieved a high validity score of 89% from expert validators. Teacher and student responses were also highly positive, scoring 88% and 91% respectively. The large-scale trial revealed statistically significant improvements (t-test, p 0.05) in both collaborative and problem-solving skills. N-Gain analysis showed a moderate increase in problem-solving ability in the experimental group (0.56), compared to a low increase in the control group (0.30). The findings indicate that PBL-based LKPD effectively enhances collaborative and problem-solving skills. This instructional approach supports deeper understanding and engagement in complex chemistry topics, offering a scalable model for science education.